Effect of Quenching Temperature on Microstructure and Wear Resistant Properties of Mo2FeB2 Cermet Coating - Hao Zhang; Yongqi Hu; Yang Zhang (Lubricants, 2025)
H13 steel, a widely used material in hot work tooling, faces premature failure due to insufficient hardness and wear resistance. To address this limitation, Mo2FeB2 cermet coatings were fabricated on H13 alloy steel via plasma spray welding, and subsequently quenched at 850 °C, 1000 °C, and 1150 °C. The effects of the quenching temperature on the microstructure and wear resistance were investigated using optical microscopy (OM) for cross-sectional morphology, scanning electron microscopy (SEM) for microstructural and wear surface analyses, energy-dispersive spectroscopy (EDS) for elemental composition analysis, and X-ray diffraction (XRD) for phase identification. The coating primarily consisted of α-Fe, Mo2FeB2, (Mo,Fe,Cr)3B2, and Fe23(B,C)6 phases. Increasing the temperature to 1150 °C increased the Mo2FeB2 hard phase and elevated microhardness by 32.04% (from 827 HV0.5 to 1092 HV0.5). Wear resistance improved by 46.38% (mass loss reduced from 6.9 mg to 3.7 mg). The main wear mechanism was identified as abrasive wear due to the spalling of hard phase particles. These results demonstrate that optimizing quenching temperature enhances the hardness and wear resistance in Mo2FeB2 coatings, offering a viable strategy to extend H13 steel service life in high-temperature industrial applications.